2007
DOI: 10.1111/j.1399-3054.2007.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analyses give insights into selenium‐stress responses and selenium tolerance mechanisms in Arabidopsis

Abstract: Selenate is chemically similar to sulfate and can be taken up and assimilated by plants via the same transporters and enzymes. In contrast to many other organisms, selenium (Se) has not been shown to be essential for higher plants. In excess, Se is toxic and restricts development. Both Se deficiency and toxicity pose problems worldwide. To obtain better insights into the effects of Se on plant metabolism and into plant mechanisms involved in Se tolerance, the transcriptome of Arabidopsis plants grown with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
134
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(155 citation statements)
references
References 56 publications
12
134
0
9
Order By: Relevance
“…The above-mentioned studies showed no indication that ethylene plays a role in S deficiency responses. However, a recent comprehensive gene expression analysis showed that transcripts regulating ethylene synthesis (ACS6) and signaling (ERF) were up-regulated by selenate treatment, and plants overexpressing ERF1 exhibited an increase in selenate resistance (Van Hoewyk et al, 2008). These results indicate that Se resistance achieved through ethylene signaling is not mediated by S star- vation resulting from the Se treatment but is a Se-specific response.…”
Section: Resultsmentioning
confidence: 60%
“…The above-mentioned studies showed no indication that ethylene plays a role in S deficiency responses. However, a recent comprehensive gene expression analysis showed that transcripts regulating ethylene synthesis (ACS6) and signaling (ERF) were up-regulated by selenate treatment, and plants overexpressing ERF1 exhibited an increase in selenate resistance (Van Hoewyk et al, 2008). These results indicate that Se resistance achieved through ethylene signaling is not mediated by S star- vation resulting from the Se treatment but is a Se-specific response.…”
Section: Resultsmentioning
confidence: 60%
“…Ethylene directly induces the activity of the key enzyme of sulfate assimilation, adenosine 59-phosphosulfate reductase (APR), and ethylene signaling is important for the regulation of this enzyme by salt (Koprivova et al, 2008). Arabidopsis mutants in ethylene signaling are more sensitive to selenium, which primarily affects sulfate uptake and assimilation (Van Hoewyk et al, 2008). Ethylene production is affected by nitrate supply, and ethylene signaling is involved in the regulation of nitrate transporters (Zheng et al, 2013), showing a general role of this phytohormone in the control of plant nutrition.…”
Section: Genes Potentially Affecting Anion Homeostasismentioning
confidence: 99%
“…Incidentally, an increase in cytosolic calcium concentration is also expected in these plants since many genes related to calcium signaling, such as calcium transporters, calcium binding proteins and calmodulin genes, were identified in the transcriptome analysis of selenate-treated plants. 7 The Se-induced ROS mimic an oxidative burst in plant cells, and the perception of this change triggers a wide array of signaling cascades similar to those induced by plant pathogens. Furthermore, Se-induced changes in the levels of free calcium may phosphorylate one of the subunits of NADPH-oxidase known to generate ROS, or it may directly affect NADPH oxidase activity because this enzyme has an N-terminal sequence with two calcium-binding EF-hand motifs.…”
mentioning
confidence: 99%
“…These mutants showed less resistance to selenite and selenate than wildtype plants. 1,7 Conversely, treatment of MeJA or 1-aminocyclopropane-1-carboxylic acid (ACC; precursor of ethylene) enhanced selenite resistance in a Se-sensitive Arabidopsis ecotype, Ws-2. 1 These results further suggest that ethylene and JA are important for Se resistance in plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation